2022
DOI: 10.3389/fonc.2022.963314
|View full text |Cite
|
Sign up to set email alerts
|

Urolithin A targets the AKT/WNK1 axis to induce autophagy and exert anti-tumor effects in cholangiocarcinoma

Abstract: Urolithin A (UA; 3,8-dihydroxybenzo[c]chromen-6-one), a metabolite generated by intestinal bacteria during the biotransformation of ellagitannins, has gained considerable attention in treating several cancers. Cholangiocarcinoma (CCA) remains one of the most lethal cancers; it grows in a special environment constantly exposed to both blood and bile. Since UA is known to undergo enterohepatic recirculation, we hypothesized that UA might have significant antitumor effects in CCA. Here, we investigated the therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Regarding WNK1, Sahashi et al recently reported that urolithin A induces autophagy and exerts anti-tumor effects by regulating WNK1. 33 TBE contains high levels of ellagitannins, which are hydrolyzed to produce ellagic acid, 23 and the intestinal metabolite of ellagic acid is urolithin. 34 The fact that the main component of TBE is closely related to urolithin is important when considering the mechanism of action of TBE.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding WNK1, Sahashi et al recently reported that urolithin A induces autophagy and exerts anti-tumor effects by regulating WNK1. 33 TBE contains high levels of ellagitannins, which are hydrolyzed to produce ellagic acid, 23 and the intestinal metabolite of ellagic acid is urolithin. 34 The fact that the main component of TBE is closely related to urolithin is important when considering the mechanism of action of TBE.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies focused on the antineoplastic impacts of UA supplementation [ 8 , 9 , 24 ]. Zhao et al investigated the impacts of UA in SW620 colorectal cancer cells [ 8 ].…”
Section: Reviewmentioning
confidence: 99%
“…The final study analyzed in this review was a human cell line study completed by Sahashi et al [ 24 ]. This study utilized HuCCT-1 and SSP-25 cells to model cholangiocarcinoma (CCA) in vitro and investigated UA treatment’s impacts in the neoplastic setting [ 24 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations